Assessment of groundwater facies in Wates Coastal Area, Kulon Progo, Yogyakarta, Indonesia - Phyu Phyu Thin; Heru Hendrayana; Wahyu Wilopo; Satoru Kawasaki (Journal of Degraded and Mining Lands Management, 2018)
The groundwater quality in Wates coastal area is generally a good category but there are high salinity values at some locations. The chemical quality of groundwater from place to place is different. The difference of water quality is a major problem in the study area. A total of 27 groundwater samples were collected in August, 2017. Geochemical signatures of groundwater were used to analyze the major ionic concentrations in the groundwater, to identify the dominant hydrogeochemical processes, and to determine the relationship between groundwater flow and spatial distribution of water types. Hierarchical Cluster analysis and Schoeller diagram, Gibbs plots, Scatter diagrams, and Piper Trilinear diagram were employed to evaluate the hydrogeochemical evolution of groundwater. In Schoeller diagrams, the relative tendency of ions in meq/L shows Na+ > Mg2+> Ca2+> K+ and HCO3- >Cl- > SO42-trends, typically in saline water. Gibbs diagram reveals that the groundwater chemistry is mainly controlled by rock weathering with secondary contribution from evaporation source. Based on the results of Hierarchical Cluster analysis and Piper diagram, dominant hydrogeochemical facies in the study area are Ca-HCO3, Na-Cl, and Ca-Na-HCO3 types. Ca-HCO3 facies are almost throughout the study area and the evolution of groundwater was mainly controlled by the silicate weathering process. Na-Cl water types are grouping in the study area influenced by cation exchange and evaporation processes, while Ca-Na-HCO3 types are locally grouping with silicate weathering and cation exchange processes. The geology implies that common silicate minerals are found everywhere in the study area. In fact, the distributions of groundwater facies are related to the local geology, which may result in different hydrochemical processes. In addition, lithology is very influential on the existence of groundwater in the study area